KERAGAMAN BUDAYA LOKAL DALAM PEMBANGUNAN KARAKTER BANGSA - I Nyoman Temon Astawa (Pangkaja: Jurnal Agama Hindu, 2022)
Indonesian culture is a common culture owned by the Indonesian people which is the highest peak of regional cultures. National culture itself has many forms because basically it comes from various types and styles, but that is not a problem because with that our nation has its own characteristics. In order to maintain and maintain the existence of our nation's culture, we can do many things such as holding competitions and seminars that breathe national culture so that our culture will be protected from adversity due to competition with foreign cultures. And in responding to the existing diversity, we must be able to reflect on the core of our diverse culture because basically everything is based on the Pancasila ideology. To deal with the negative impacts of cultural diversity, of course, it is necessary to develop various attitudes and understandings that can eliminate misunderstandings and build a fortress of mutual understanding. An interesting idea to be raised in this context is multiculturalism and the attitude of tolerance and empathy. The transformation of local cultural values as a means to build the nation's character and philosophically is a basic need in the nation's process because only a nation that has a strong character and identity will exist. Meanwhile, ideologically, the role of development in national culture is an effort to manifest the Pancasila ideology in the life of the nation and state. Normatively, the development of the nation's character is a concrete manifestation of the steps to achieve the country's goals in preserving cultural diversity, especially in Indonesia.